Predisposing factors for laryngeal hyperfunction dysphonia in adult patients. Hospital Universitario Dr. Luis Gómez López (Boletin Médico de Postgrado, 2020)
A retrospective review of 95 medical charts was carried out with the objective of determining the predisposing factors for laryngeal hyperfunction dysphonia in adult patients attending the otorhinolaryngology consult of the Hospital Universitario Dr. Luis Gómez López, during the period January-December 2016 to June 2017. The results show a male predominance (82.4%) and an age between 37 to 44 years in 96.8% of cases; 38% of patients are professionals exposed to environmental pollution and 25% are voice professionals; 79% of patients don’t smoke; 38% of cases abuse voice by speaking frequently, singing and shouting. 67.4% of patients have been exposed to vapors, 86.3% to tobacco smoke and 82.1% to firewood. Degree of dysphonia diagnosed by nasofibrolaryngoscopy was grade II (60%). Early detection of predisposing factors associated to laryngeal hyperfunction dysphonia is important in order to implement environmental actions to mitigate their influence in voice physiology.
Keywords: dysphonia; laryngeal hyperfunction; otorhinolaryngology; smoking; nasofibrolaryngoscopy